Accommodating the Syllabus to Visually Impaired Students in the English Language Classroom: Challenges and Concerns - Martínez-Hernández, Ana-Isabel; Bellés-Fortuño, Begoña (International Journal of English Studies, 2021)
The inclusion of students with disabilities in the education system results in content or assessment accommodations to suit the students’ special needs and to ensure they have acquired the objectives listed in the curriculum. In this paper, we aim at proposing different ways to accommodate a university English language test to a partially blind student who used text-to-speech tools (TTS) in order to provide them with accurate assessment. To carry out this research, the student has been monitored throughout the course to see which accommodations fit their1 needs best. All in all, we have observed that read-aloud accommodations lead to a better inclusion of the partially sighted student and better performance.